Aggressiveness and Libido of Male Mus musculus L. in Ethanol Extract of Red Ginger (Zingiber officinale Roxb. var. Rubrum) - Nida Nurhanifah; Sutyarso Sutyarso; M. Kanedi; Hendri Busman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
The residue of paraquat herbicides may cause human health problems. Paraquat causes the testosterone hormone to decline. Testosterone hormone affects aggressive and sexual behavior. It is caused by free radicals in the body. Free radicals can be non-reactive if in the body there are antioxidants. Red ginger could be used as an antioxidant because it has active phenolic compounds, such as arginine, gingerol, shogaol, zingerone, gingerdiol, and zingiber. Ginger could increase serum testosterone levels. The purpose of this research is to know the effect of red ginger ethanol extract on aggressiveness and libido of male mice induced by paraquat herbicide. This study used a Completely Randomized Design (RAL) consisting of six treatment groups with four replications each. Group P1 as control (aqua dest), P2 (paraquat at dose 20 mg/kg BM), P3, P4, P5 (paraquat with dose 20 mg/kg BM and red ginger extract at 200 mg/kg BM, 400 mg/kg BM, 600 mg/kg BM) and P6 (red ginger extract at 600mg/kg BM). Paraquat is given 2 times a week for 21 days and the red ginger extract is given daily for 35 days. The result of analysis with One-way ANOVA and continued BNT at 5% showed that giving of red ginger ethanol extract can increase aggressive behavior and libido of male mice induced paraquat herbicide.